Structural and functional changes of the cerebellum in temporal lobe epilepsy - Wang, Ge; Liu, Xianghe; Zhang, Min; Wang, Kangrun; Liu, Chaorong; Chen, Yayu; Wu, Wenyue; Zhao, Haiting; Xiao, Bo; Wan, Lily; Long, Lili (Frontiers in Neurology, 2023)
Aims This study aimed to comprehensively explore the cerebellar structural and functional changes in temporal lobe epilepsy (TLE) and its association with clinical information. Methods The SUIT toolbox was utilized to perform cerebellar volume and diffusion analysis. In addition, we extracted the average diffusion values of cerebellar peduncle tracts to investigate microstructure alterations. Seed-based whole-brain analysis was used to investigate cerebellar–cerebral functional connectivity (FC). Subgroup analyses were performed to identify the cerebellar participation in TLE with/without hippocampal sclerosis (HS)/focal-to-bilateral tonic–clonic seizure (FBTCS) and TLE with different lateralization. Results TLE showed widespread gray matter atrophy in bilateral crusII, VIIb, VIIIb, left crusI, and left VIIIa. Both voxel and tract analysis observed diffusion abnormalities in cerebellar afferent peduncles. Reduced FC between the right crus II and the left parahippocampal cortex was found in TLE. Additionally, TLE showed increased FCs between left lobules VI–VIII and cortical nodes of the dorsal attention and visual networks. Across all patients, decreased FC was associated with poorer cognitive function, while increased FCs appeared to reflect compensatory effects. The cerebellar structural changes were mainly observed in HS and FBTCS subgroups and were regardless of seizure lateralization, while cerebellar–cerebral FC alterations were similar in all subgroups. Conclusion TLE exhibited microstructural changes in the cerebellum, mainly related to HS and FBTCS. In addition, altered cerebellar–cerebral functional connectivity is associated with common cognitive alterations in TLE.